RH rapid decarbonization process based on data statistics and off-gas analysis - GUO Jian-long; BAO Yan-ping; WANG Min; LI Ying-jiang (工程科学学报, 2018)
Reasonable process parameters in the RH refining process are very important to improve the decarburization rate and shorten the refining time.In view of the problem of long decarburization time of 300-t RH in the IF steel production, SPSS statistical software was used to analyze the correlation relationship between the process parameters of the RH refining process and the decarburization time.Based on large numbers of refining process date statistics and off-gas analysis, the relationship between the process parameters and decarburization time was obtained and the improvement measures were put forward.The results show that the limit vacuum should be reached as early as possible and pressure drop platform should be avoided in the refining process;the addition amount of carbon powder should be no more than 35 kg, the join number should be no more than 2 times and the carbon powder should be added as soon as possible before reaching the ultimate vacuum pressure;oxygen blowing should be controlled before the peak value of CO, and the start time of oxygen blowing should be controlled in the range of 2.5-3.5 min.Through industry technology verification, the average decarburization time is reduced from 21.4 to 18.3 min after the optimization of process parameters, decreasing amplitude reaches14.5%.